2022
DOI: 10.1097/htr.0000000000000780
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury History Among Individuals Using Mental Health and Addictions Services: A Scoping Review

Abstract: Objective: Traumatic brain injury (TBI) has been increasingly linked in population research to psychiatric problems as well as substance use and related harms, suggesting that individuals with TBI may also present more frequently to mental health and addictions (MHA) services. Little is known, however, about TBI history among MHA service users. The objectives of this review were to understand (i) the prevalence of TBI history among MHA service users; (ii) how TBI history is identified in MHA service settings; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…However, identifying, testing, and specifying the mechanisms through which these implementation strategies operate on EBP adoption are necessary to reduce implementation costs and expedite the public health benefit of EBPs through more precise implementation approaches. Nonetheless, given that over half of clients in behavioral healthcare settings have a lifetime exposure to TBI that affects their ability to fully engage in and benefit from treatment [ 3 , 74 ], tailored training and educational strategies are important first steps to changing the treatment landscape.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, identifying, testing, and specifying the mechanisms through which these implementation strategies operate on EBP adoption are necessary to reduce implementation costs and expedite the public health benefit of EBPs through more precise implementation approaches. Nonetheless, given that over half of clients in behavioral healthcare settings have a lifetime exposure to TBI that affects their ability to fully engage in and benefit from treatment [ 3 , 74 ], tailored training and educational strategies are important first steps to changing the treatment landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Translating this screening method from research into practice is particularly challenging because TBI is often viewed as a medical condition to be identified and addressed by medical professionals. Although TBI does sometimes require intensive medical intervention to address the physical effects of the injury (i.e., neuroendocrine dysfunction or subdural hematoma, for example), vast evidence has demonstrated that TBI can result in chronic cognitive, behavioral, and psychiatric conditions over the life course [ 84 , 85 ], which disproportionately affects individuals who seek care in behavioral health settings [ 3 ]. Despite how common TBI is in these settings, behavioral health providers often do not receive any formal education on TBI and hence enter the workforce unaware about the presence of TBI among clients or their roles in addressing these clients’ needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70%–90%), TBI is considered mild (mTBI) with a Glasgow Coma Scale score of 13–15 2,3 . Following TBI, patients frequently present neuropsychiatric problems (e.g., depression, anxiety) and substance abuse as a post‐TBI sequel 4,5 . In turn, previous mental health problems or substance abuse elevate a person's risk of experiencing TBI 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Following TBI, patients frequently present neuropsychiatric problems (e.g., depression, anxiety) and substance abuse as a post-TBI sequel. 4,5 In turn, previous mental health problems or substance abuse elevate a person's risk of experiencing TBI. [6][7][8] So far, the impact of a patient's stress load before TBI has been largely neglected when predicting outcomes following mTBI.…”
Section: Introductionmentioning
confidence: 99%